Information dissemination of local content through Muhi Corner in Muhammadiyah 1 Yogyakarta High School Library - Zeni Istiqomah (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2022)
Background of the study: The library of SMA Muhammadiyah 1 Yogyakarta has a unique and distinctive collection that is referred to as local content and organized in Muhi Corner. Libraries have a duty to collect and disseminate them to users Purpose: This study aims to analyze the local content information service of Muhi Corner, analyze the information dissemination process carried out, and evaluate the obstacles in the dissemination of information. Method: This study uses a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation analysis. The data analysis was conducted by data reduction, data presentation, and conclusion. Findings: The results showed that Information dissemination activities for Muhi Corner's collections started with information dissemination for teachers, education staff, students, and researchers; then packaged in the form of print and digital papers. Information sources are presented in the form of local collections and gray literature. The information channels used are direct (socialization & library tour) and social media (Instagram). Conclusion: Dissemination of information on the Muhi Corner collection has been carried out but is still limited, either directly or using the media. Obstacles in disseminating Muhi Corner information include, (1) limited human resources, (2) limited collection on the subject of literature, and (3) limited promotional activities.